2016
DOI: 10.15171/hpp.2015.029
|View full text |Cite
|
Sign up to set email alerts
|

Smoke-Free Universities Help Students Avoid Establishing Smoking by Means of Facilitating Quitting

Abstract: Background: This study aimed to clarify whether smoke-free policies affect the initiation or the quitting of smoking among young adults. Methods: In this natural quasi-experiment study, three universities with different enforcement of smoke-free policies were considered in Kazan City, Russian Federation. Exposure data were collected in 2008-2009 through measurement of particulate matter concentrations in typical sets of premises in each university to distinguish smoke-free universities (SFU) and those not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…We found that the smoking prevalence at SFCs (5.2%) and NSFCs (6.7%) was not much different. Nonetheless, similar to another study in Kazan city that compared SFCs and NSFCs, 36 SFCs had a lower smoking prevalence than NSFCs descriptively. Other studies have also reported low smoking prevalence in universities that implement SFC policies, for example, 9.2% in the USA 37 and 8.4% in Thailand, 24 due to decreases in smoking behaviour.…”
Section: Discussionsupporting
confidence: 81%
“…We found that the smoking prevalence at SFCs (5.2%) and NSFCs (6.7%) was not much different. Nonetheless, similar to another study in Kazan city that compared SFCs and NSFCs, 36 SFCs had a lower smoking prevalence than NSFCs descriptively. Other studies have also reported low smoking prevalence in universities that implement SFC policies, for example, 9.2% in the USA 37 and 8.4% in Thailand, 24 due to decreases in smoking behaviour.…”
Section: Discussionsupporting
confidence: 81%
“…Smokers account for 24% of the dental students, compared with 13% in a school in the capital of the country and in other places. 25,27,28 In our sample, women account for 24% and men for 76% of the smokers, which is similar to the distribution in other schools. 25,27,28,31 In our study, we found that 25 to 39% of dental students are exposed to SHS either at their home, at their friends' houses, or at the university.…”
Section: Discussionsupporting
confidence: 80%
“…24 A Russian study concluded that smoke-free universities help young adults avoid initiating regular smoking. 25 A Vietnamese study reported that positive changes in knowledge and attitude toward smoke-free universities were associated with the adoption of tobacco control legislation. 26 Several studies have investigated the attitudes toward a smoke-free policy in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, replacing waterpipe smoking with another family activity can diminish the spread of WTS among Iranian families as can considering prevention as a high priority for socio-economically disadvantaged families, and introducing the courses at schools to increase awareness of health risks and side effects of WTS. 4 , 9 , 13 , 23 , 30 31 - 33 Also, the lack of evidence-based studies for developing health warning labels is another challenge in preventing WTS among youth.…”
Section: Dear Editormentioning
confidence: 99%